Effect of the Structure of Therapeutic Adenosine Analogues on Stability and Surface Electrostatic Potential of their Complexes with Poly(propyleneimine) Dendrimers - Gorzkiewicz, Michal; Appelhans, Dietmar; Boye, Susanne; Lederer, Albena; Voit, Brigitte; Klajnert-Maculewicz, Barbara (Macromolecular Rapid Communications, 2019)
Poly(propyleneimine) glycodendrimers are proposed as nanocarriers for triphosphate forms of anticancer adenosine analogues to improve the efficiency of chemotherapy and to overcome drug resistance mechanisms. This approach has proven successful for fludarabine administration—an autonomous way of cellular entry of a nucleotide–dendrimer noncovalent complex enables an increase in the intracellular accumulation and cytotoxic activity of the active metabolite of the drug. However, the attempt to apply an analogous strategy for clofarabine results in the inhibition of drug activity. To better understand this phenomenon, characterization and comparison of drug-dendrimer complexes were needed to indicate the differences in their surface properties and the strengths of fludarabine-dendrimer and clofarabine-dendrimer interactions. Here, zeta potential measurements, ultrafiltration, and asymmetric flow field-flow fractionation are applied to determine the surface electrostatic potential and stability of nucleotide–dendrimer formulations. This approach significantly extends the authors’ research on the complexation potential of perfectly branched macromolecules, ultimately explaining previously observed differences and their consequences.
CRIS-Team Scopus Importer:2022-04-14
Keywords: clofarabine; complexation; drug delivery systems; fludarabine; PPI glycodendrimers